OSMOREGULASI PADA HEWAN AKUATIK - Lantu, Sartje (Sam Ratulangi University, 2010)
All aquatic organisms must deal with the problem of maintaining internal homeostasis, a constant internal chemical environment in which that organism's enzymes can operate efficiently. Â As we saw earlier, this is largely a matter of osmoregulation, but other factors are involved also. Â Many marine organisms can get by with minimal osmoregulation since the oceans, where the enzymes evolved, are already a good environment; other marine organisms maintain their body fluids at ionic concentrations different from the surrounding ocean and must actively regulate ions. Â Freshwater also calls for active measures to maintain proper osmotic balance.